The use and safety risk of repurposed drugs for COVID-19 patients: lessons learned utilizing the Food and Drug Administration's Adverse Event Reporting System - Deemah S. Alsuhaibani; Heba H. Edrees; Thamir M Alshammari (Elsevier, 2023)
Objectives: This study was designed to assess the disproportionality analyses of adverse drug reactions (ADRs) related to hydroxychloroquine and remdesivir and how ADR reporting fluctuated during the COVID-19 pandemic. Methods: A retrospective observational study was conducted utilizing the Food and Drug Administration's Adverse Event Reporting System (FAERS) data between 2019 and 2021. The study was conducted in two phases. In the first phase, all reports associated with the drugs of interest were evaluated to assess all related adverse drug reactions. In the second phase, specific outcomes of interest (i.e., QT prolongation and renal and hepatic events) were determined to study their association with the drugs of interest. A descriptive analysis was conducted for all adverse reactions related to the drugs being studied. In addition, disproportionality analyses were conducted to compute the reporting odds ratio, the proportional reporting ratio, the information component, and the empirical Bayes geometric mean. All analyses were conducted using RStudio. Results: A total of 9,443 ADR reports related to hydroxychloroquine; 6,160 (71.49) patients were female, and higher percentage of patients of both sexes were over the age of 65 years. QT prolongation (1.48%), pain (1.38%), and arthralgia (1.25%) were most frequently reported ADRs during the COVID-19 pandemic. The association of QT prolongation with use of hydroxychloroquine was statistically significant (ROR 47.28 [95% CI 35.95-62.18]; PRR 42.41 [95% CI 32.25-55.78]; EBGM 16.08; IC 4.95) compared with fluoroquinolone. The outcome was serious medical events in 48.01% of ADR reports; 27.42% required hospitalization and 8.61% resulted in death. Of 6,673 ADR reports related to remdesivir, 3,928 (61.13%) patients were male. During 2020, the top three ADR reports were elevated liver function tests (17.26%), acute kidney injury (5.95%) and death (2.84%). Additionally, 42.71% of ADR reports indicated serious medical events; 19.69% resulted in death and 11.71% indicated hospitalization. The ROR and PRR of hepatic and renal events associated with remdesivir were statistically significant, (4.81 [95% CI 4.46-5.19] and 2.96 [95% CI 2.66-3.29], respectively. Conclusion: Our study showed that several serious ADRs were reported with the use of hydroxychloroquine, which resulted in hospitalization and death. Trends with the use of remdesivir were similar, but to a lesser extent. Therefore, this study showed us that off-label use should be based on thorough evidence-based evaluation.